2015
DOI: 10.1123/jsep.2014-0303
|View full text |Cite
|
Sign up to set email alerts
|

Biological Evidence of Imagery Abilities: Intraindividual Differences

Abstract: This study extended motor imagery theories by establishing specificity and verification of expected brain activation patterns during imagery. Eighteen female participants screened with the Movement Imagery Questionnaire-3 (MIQ-3) as having good imagery abilities were scanned to determine the neural networks active during an arm rotation task. Four experimental conditions (i.e., KINESTHETIC, INTERNAL Perspective, EXTERNAL Perspective, and REST) were randomly presented (counterbalanced for condition) during thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 42 publications
3
25
1
Order By: Relevance
“…Finally, it is important to note that the participants with national or international levels of practice, 10 years of practice, and a high frequency of practice had higher EVI than IVI scores. According to Callow, Jiang, Roberts, and Edwards (2017), the use of EVI and IVI might exert influences on the motor system, resulting in selectively different brain activations (Jiang et al, 2015;Lorey et al, 2009;Ruby & Decety, 2001;Seiler et al, 2015) that depend on task constraints (Hardy & Callow, 1999). For example, White and Hardy (1995) showed that EVI was efficient in the learning of movements, including body coordination or form to reproduce (e.g., gymnastics), whereas IVI was beneficial for open skills when timing is important (e.g., slalom line-based activities such as downhill slalom skiing).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, it is important to note that the participants with national or international levels of practice, 10 years of practice, and a high frequency of practice had higher EVI than IVI scores. According to Callow, Jiang, Roberts, and Edwards (2017), the use of EVI and IVI might exert influences on the motor system, resulting in selectively different brain activations (Jiang et al, 2015;Lorey et al, 2009;Ruby & Decety, 2001;Seiler et al, 2015) that depend on task constraints (Hardy & Callow, 1999). For example, White and Hardy (1995) showed that EVI was efficient in the learning of movements, including body coordination or form to reproduce (e.g., gymnastics), whereas IVI was beneficial for open skills when timing is important (e.g., slalom line-based activities such as downhill slalom skiing).…”
Section: Discussionmentioning
confidence: 99%
“…MI is frequently used to facilitate motor (re)learning, promote motor rehabilitation, and improve performance in sports settings Rulleau, Mauvieux, & Toussaint, 2015). Seiler, Monsma, and Newman-Norlund (2015) argued that the effectiveness of MI as a performance-enhancing strategy might primarily depend on one's capacity to generate accurate and vivid mental images of specific movements. Participants with greater imagery ability have been shown to achieve greater levels of performance following MI practice than their less-skilled counterparts (Goss, Hall, Buckolz, & Fishburne, 1986;Hall, Buckolz, & Fishburne, 1992;Robin et al, 2007;Robin & Coudevylle, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This theory hypothesises that the motor system is part of a cognitive network that includes various psychological activities. Initial functional MRI investigations have shown that similar neural pathways are activated during cognitive training and actual performance of a task [12,14]. Furthermore, a study by Debarnot et al found that the brain changes resulting from cognitive training for a specific motor task mimic those observed after physical practice of the same skill [12,15].…”
Section: What Is Cognitive Training?mentioning
confidence: 99%
“…A reason discussed for its effectiveness resides in Janerod's simulation theory [15] which hypotheses that the motor system is also part of a bigger cognitive network which includes various psychological activities. During this 'Mental Training', similar neural pathways are activated and similar changes in the brain take place as when actually performing a motor skill as functional MRI investigations have shown [15,16]. This explains why 'Mental Training' can directly improve motor skills and induce a similar neuroplasticity as physical practice and thus can help to close the gap between the observation and the execution of a skill [17].…”
Section: Introductionmentioning
confidence: 99%